Analisa Semiotik Makna Pesan Iklan Mendorong Mobil Partai Solidaritas Indonesia - Riza Julfaniah (LPPM Stikosa-AWS, 2022)
This study was to determine the meaning of the message conveyed in the PSI Solidaritas Indonesia advertisement version of